Hibiscus Mutabilis‐Inspired Upcycled TPEE Films with Orthogonal Wavelength‐Controlled Spiropyrans for Dynamic Anticounterfeiting and Photoswitchable Conductivity - Chen, Yi‐Fan; Lee, Lin‐Ruei; Chang, Ming‐Hsuan; Lin, Huan‐Wei; Liu, Yu‐Chun; Chang, Chun‐Ting; Kuo, Kai‐Chuan; Chang, Chun‐Chi; Lin, Che‐Tseng; Chen, Jiun‐Tai (Small (Weinheim an der Bergstrasse, Germany), 2025)
Plastics are integral to modern life but contribute significantly to environmental pollution due to their durability and low recycling rates. Poly(ethylene terephthalate) (PET) is particularly problematic, representing a substantial portion of global plastic waste. Addressing this issue, this work presents a sustainable approach to upcycle PET into thermoplastic polyester elastomer (TPEE) films, integrated with orthogonal wavelength‐controlled spiropyran derivatives, SP‐COOH and MC‐SO 3 . These upcycled TPEE films exhibit dynamic anticounterfeiting and photoswitchable conductivity properties. The spiropyran derivatives demonstrate reversible structural changes and color variations under different light conditions, enhancing their mechanical properties and solvent resistance. Inspired by the color changing of Hibiscus mutabilis , this work also demonstrates the artificial light‐induced color on the petals of moth orchids. The incorporation of conductive poly(3,4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) further enables photoswitchable conductivity, offering a dual‐layered security feature. This work not only advances polymer upcycling but also introduces innovative applications in anticounterfeiting and wearable technology, aligning with global sustainability goals and demonstrating the potential for high‐value product development from waste materials.